Knockdown of SP1/Syncytin1 axis inhibits the proliferation and metastasis through the AKT and ERK1/2 signaling pathways in non‐small cell lung cancer. (9th August 2019) - Li, Xiaohui; Fu, Yang; Xia, Xiyan; Zhang, Xin; Xiao, Ke; Zhuang, Xuewei; Zhang, Yi
Abstract: Syncytin 1 is considered as an oncogene in various malignant tumors, but its effect on non‐small cell lung cancer (NSCLC) has not been reported. We investigated the specific role of Syncytin 1 on NSCLC through the transfection of Syncytin 1 knockdown or overexpression plamids in A549 cells. Our results proved that knockdown of Syncytin 1 inhibited the proliferation, and blocked the cell cycle on G1 phase by inhibiting the expression of Nusap1, Cyclin D1, CDK6, and CDK4. Cell cycle arrest also leaded to increased apoptosis in Syncytin 1 knockdown cells. Suppression of Syncytin 1 inhibited the migration and invasion, as well as the expressions of epithelial‐mesenchymal transition (EMT) makers, N‐cadherin, β‐catenin, and Vimentin, indicating that Syncytin 1 knockdown inhibited the metastasis via reversing the EMT process in A549 cells. The phosphorylation levels of Akt, mTOR, and Erk1/2 were all decreased in Syncytin 1 knockdown cells, suggesting the signaling pathways by which Syncytin 1 operated as an oncogene in NSCLC. Moreover, the underexpression of transcription factor SP1 downregulated the Syncytin 1 expression in A549 cells. The rescue experiment of Syncytin 1 in SP1 knockdown cells further proved that Syncytin 1 could block the inhibition of cell growth induced by SP1 knockdown. In conclusion, knockdown of SP1/Syncytin1 axis inhibited the progression of NSCLC by the reversion of tumor epithelial‐mesenchymal transition process and suppression of Akt and Erk signaling pathways, suggesting that they are potential targets for targeted therapy of NSCLC. Abstract : We investigated the specific role of Syncytin 1 on non‐small cell lung cancer (NSCLC) through the transfection of Syncytin 1 knockdown or overexpression plamids in A549 cells. Knockdown of SP1/Syncytin1 axis inhibited the progression of NSCLC by the reversion of tumor epithelial‐mesenchymal transition process and suppression of Akt and Erk signaling pathways, suggesting that they are potential targets for targeted therapy of NSCLC.